2001
DOI: 10.1002/1099-0682(200106)2001:6<1515::aid-ejic1515>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Two-Level Self-Organisation of Arrays of [2×2] Grid-Type Tetranuclear Metal Complexes by Hydrogen Bonding

Abstract: Here we report on the synthesis and characterisation of four new complexes of the [2×2] M 4 II grid-type (M = Co, Fe, Zn) with oligopyridine-derived ligands. The presence of aminopyrazine and aminopyrimidine moieties at the edge of the ligands potentially enables the formation of infinite hydrogen-bonded multi-grid networks. The ligands were synthesised by subsequent stannylations and Stille-type coupling reactions. The complexes were obtained by self-assembly of the ligand with the metal salt. The single-crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…Successful complex formation could be shown by NMR spectroscopy and ESI mass spectrometry and was consistent with earlier examples of non‐functionalized BTP grid complexes. Due to structural similarities, it was possible to assign NMR signals through comparison with these previously published compounds.…”
Section: Resultssupporting
confidence: 66%
“…Successful complex formation could be shown by NMR spectroscopy and ESI mass spectrometry and was consistent with earlier examples of non‐functionalized BTP grid complexes. Due to structural similarities, it was possible to assign NMR signals through comparison with these previously published compounds.…”
Section: Resultssupporting
confidence: 66%
“…One route to polymetallic compounds-a route perhaps best termed ™designed assembly∫-controls the reaction pathway by making a specific metal ± ligand interaction the most significant in the system. Typical examples of this approach are the grids made by Lehn and co-workers, [1,2] the sophisticated structures made by the Saalfrank group [3,4] or the polyhedra constructed by Fujita and co-workers based on the concept of ™molecular panelling∫. [5] A complementary strategy is ™serendipitous assembly∫, [6] where the variables in the complex system are modified following certain rationales to influence the product found, rather than to control or design the target molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The structure in the crystal of [Ni 8 K 2 (OH) 4 (ppo) 4 (piv) 10 -(Hppo) 2 (Hpiv) 2 (MeCN) 2 ] (9). The hydrogen atoms and the CH 3 2 ] pseudo cubane ( Figure 6 below) with two missing edges. The m 3 -O atoms in this unit belong to OH À groups, and the m-O donors come from one carboxylate group and one ppo À ligand in the 3.21 coordination mode.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the synthetic conditions of the above Zn(II) and Cu(I) complexes with those used in the earlier [2×2] grid complexes, [6][7][8][9] we found that in order to obtain [2×2] grid complexes, one must not only select the appropriate ligand, but also choose the right metal-salt. In the earlier literature, the metal-salts were not simple ones, including [Cu(CH 3 CN) 4 ]PF 6 , Cu(CF 3 SO 3 ) 2 ·C 6 H 6 , Zn(BF 4 ) 2 , AgCF 3 SO 3 , AgBF 4 , Co(BF 4 ) 2 , Fe(BF4) 2 , Mn(ClO 4 ) 2 and so on.…”
Section: 23mentioning
confidence: 99%
“…[6][7][8][9] We wanted to fabricate two new [2×2] grid complexes through this new ligand with Zn(II) and Cu(I) ions. However, two unexpected non-grid complexes were obtained when the L reacted with ZnI 2 and CuI, including a simple Zn(II) dinuclear complex and a one-dimensional chain Cu(I) coordination polymer.…”
Section: -18mentioning
confidence: 99%